Analysis of Financial Inclusion on Female Entrepreneurship in Selected Regions of Cameroon: Centre, Littoral and West Regions - Dr. Takoutio Feudjio virginie (International Journal on Economics, Finance and Sustainable Development, 2022)
This paper examines the effects of financial inclusion on female entrepreneurship in selected region of Cameroon. The researchers used binary logit model on secondary data extracted from Cameroon Enterprise survey 2016. The results of our findings revealed that financial inclusion has positive and significant effects on female entrepreneurship in Cameroon in general and in those regions in particular. Working capital from commercial bank as well as Microfinance Institutions has positive and significant effects on female entrepreneurship. The Pseudo R-Square shows that financial inclusion indicators used account for 8.75% of variations in female entrepreneurship. Variations in female entrepreneurship in Cameroon can therefore be explained by financial inclusion. Base on the fact that our results have shown positive and significant link between financial inclusion and female entrepreneurship, the following recommendations are made to reduce barriers to financial access so as to encourage female entrepreneurship in Cameroon. The priority should first be to implement the national gender policy and to expand it to include economic empowerment, and ensure that all government ministries are required to play their part in implementing it as this will go a long way to encourage female entrepreneurship in Cameroon. Secondly Commercial bank should be more relax on their credit policies (such as co-suety, business plan, sales books in place of collateral security) so as increase female access to credit and thus, entrepreneurship.